2015
DOI: 10.1007/s12686-015-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MHC class II genes in the critically endangered European eel (Anguilla anguilla)

Abstract: Many exploited fish species are threatened with collapse and the European eel is no exception. Its abundance has declined dramatically and various reasons account for this, among them the introduction of the invasive swim bladder nematode Anguillicola crassus. For developing an adequate immune response against this parasite, variation at the genes of the major histocompatibility complex (MHC), a key component of the adaptive immune system, might be essential and assessing their diversity might provide critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 66 publications
3
21
1
Order By: Relevance
“…The importance of duplicated genes as a reservoir of raw genetic material and its contribution in evolution has been recognized for long [67], but very little is known about AMPs copy number variation and their location within amphibian genomes. Earlier studies have shown the presence of more than one MHC class II loci in several species [68][69][70], but before our study this was not described for AMPs along a latitudinal gradient in ranids.…”
Section: Copy Number and Trans-species Polymorphism Variationcontrasting
confidence: 50%
“…The importance of duplicated genes as a reservoir of raw genetic material and its contribution in evolution has been recognized for long [67], but very little is known about AMPs copy number variation and their location within amphibian genomes. Earlier studies have shown the presence of more than one MHC class II loci in several species [68][69][70], but before our study this was not described for AMPs along a latitudinal gradient in ranids.…”
Section: Copy Number and Trans-species Polymorphism Variationcontrasting
confidence: 50%
“…In this study, 25 alleles were found from 459 valid sequences. The polymorphisms of mcaIIa have been reported in many fish species (Bracamonte et al ., ; Liu et al ., ; Liu, Liu, Wang, et al ., ; Liu, Liu, Zhao, et al ., ; Shen et al ., ; Wynne et al ., ; Xu et al ., , ; Yang et al ., ). For example, 37 different mcaIIa alleles were found from the E. coioides (Yang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 25 alleles were found from 459 valid sequences. The polymorphisms of mcaIIa have been reported in many fish species (Bracamonte et al, 2015; al., 2016). These results indicate that the mcaIIa gene is highly polymorphic in fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the utility of dN/dS ratios to detect balancing selection depends on the degree of polymorphism within species, as saturation of synonymous sites may lead to biased dN/dS estimations in highly divergent allelic lineages (Castric and Vekemans 2007;Fijarczyk and Babik 2015). Thus, these limitations should be openly acknowledged and further tested, as nucleotide substitution rates remain among the most popular measures of balancing selection acting on MHC genes, even at the level of a single species or population (e.g., Knafler et al 2014;Bracamonte et al 2015;Eimes et al 2015;Jaeger et al 2016;Jarvi et al 2016).…”
Section: Discussionmentioning
confidence: 99%